An Onomastic and Prosopographic Forest: ʿAbdīmilku in Texts from Ras Shamra–Ugarit and Ras Ibn Hani - Pardee, Dennis (Maarav, 2023)
The Ugaritic personal name ʿAbdīmilku is presented in an attempt to lay out a working template for onomastic and prosopographic research on the corpus of texts from Ras Shamra-Ugarit and the nearby site of Ras Ibn Hani. Most of the names attested in these texts appear in various types of administrative documents (economic, epistolary, legal) inscribed in the local script, alphabetic cuneiform, or in the script used internationally in the Late Bronze Age, logo-syllabic cuneiform. That name was chosen because it is well attested in texts set down in the two scripts, and a good proportion of the texts include one or more of the features useful in prosopographic identification: patronym or other family relationships, geographical or professional affiliation, and textual or archaeological data permitting an approximate dating of the text itself.